PARTISIPASI MASYARAKAT DALAM PEMBUATAN IZIN MENDIRIKAN BANGUNAN DI KECAMATAN GUBENG - Emalia, Firda Ayu (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Community participation in making building permits in Gubeng Sub-District. Building Permit is a decision of the Surabaya City Government that must be owned by each building, especially residential buildings, of course, required a regulation that serves as a controlling tool to ensure that the building will be built to ensure the safety of people who will stay in the house so that people People around the house. And the participation of the community is very little in this case, because the lack of socialization so that people still do not have the awareness to make the IMB. The purpose of this research is to find out how community participation in making IMB at Gubeng District Office. While to solve the problem researchers use qualitative research methods. The conclusion of this research is that community participation in making IMB in Gubeng Sub-district Office is still passive, lack of socialization, and lack of public awareness to make IMB and also society many do not know about procedure or procedure in making IMB and finally They forget or do not fulfill their obligation to have IMB. Â  Keywords: Participation, Building Permit.